Modification of titanium implants using biofunctional nanodiamonds for enhanced antimicrobial properties - Krok, Emilia; Balakin, Sascha; Jung, Jonas; Gross, Frank; Opitz, Joerg; Cuniberti, Gianaurelio (Giovanni) (Nanotechnology, 2020)
The present study describes a novel antimicrobial surface using anodic oxidation of titanium and biofunctional detonation nanodiamonds (ND). ND have been loaded with antibiotics (amoxicillin or ampicillin) using poly(diallyldimethylammonium chloride) (PDDA). Successful conjugation with PDDA was determined by dynamic light scattering, which showed increase in the hydrodynamic diameter of ND agglomerates and shift of zeta potential towards positive values. The surface loading of amoxicillin was determined using UV-vis spectroscopy and the maximum of 44% surface loading was obtained. Biofunctional ND were immobilized by anodic oxidation within a titanium oxide layer, which was confirmed by scanning electron microscopy. The in vitro antimicrobial properties of ND suspensions were examined using Kirby-Bauer test with E. coli. Modified titanium surfaces comprising biofunctional ND were evaluated with E. coli inoculum by live/dead assay staining. Both biofunctional ND suspensions and modified titanium surfaces presented inhibition of bacteria growth and increase in bacteria lethality.
CRIS-Team Scopus Importer:2022-04-14
Keywords: Antibiotic; Antimicrobial surface; Biomaterial; Bone implant; Detonation nanodiamond